Insights of Smart Community in Kemaman - Md Kassim, Normalini; Nathan Lurudusamy, Saravanan; Yeap Ai Leen, Jasmine; Ramayah, T.; Hazlina Hashim, Nor (International Journal of Engineering and Technology, 2018)
A smart community is regarded as a community where various next-generation technologies and advance social systems are effectively integrated and utilized, including the efficient use of energy, utilization of resources, and improvement and transformation of the everyday lives of citizens. Since technology being a major element in smart community implementation, this research focused on the identification of those research streams which are adoption and continuance of usages. The investigation targets of this research are individuals from Kemaman in Terengganu, who are existing and potential adopters of the smart community facilities, ranging from different demographic background. Preliminary information has been gathered from the local authorities such as district officers, local agencies, community leaders and local institutions. Their responses are used together with the suggestions for the Smart Community process improvement which will also be part of this study. Survey is used as the research instrument and the units of analysis are households and stakeholders who are involved in these four districts in Malaysia. As this is a quantitative study using positive epistemology, data obtained from the survey are analyzed using Partial Least Square (PLS-SEM), to test the hypotheses that explain the relationship between the constructs in a wholesome perspective. This research will conclude by recommendations that hold some insights of the usage continuance of the smart community facilities in Kemaman household context.Â Â